Training needs assessment of rice farmers in the Municipality of Siaton, Negros Oriental - Gallardo, Samuel G. (University of the Philippines in the Visayas, 2005)
The study basically follows the sustainable agriculture participatory research and extension model which essentially uses the system's approach, whereby needs assessment are being facilitated through the use of survey questionnaires and individual interviews of both the farmers and the development worker. Following the system's approach framework, relevant information on the demographic characteristics, extension programs and training needs are gathered. Presently, the average farm size ranges from 0.10 to 1.49 hectares, and the corresponding productivity level is at 51 to 70 cavans per hectare. The marginal farm sizes make it imperative to raise productivity per unit area with the application of appropriate technologies. In rice production, considering all other factors constant it is an accepted fact that a eighty(80) cavans per hectare yield is merely at breakeven.. therefore, to make rice farming profitable it is necessary to raise the level of productivity to exceed the breakeven cost and to change the farmer's outlook toward farming. He should treat rice farming as a business. in th design of trainings, emphasis on technologies that are less capital intensive is of major consideration. The ultimate aim is to increase productivity and subsequently increase farm income. The System of Rice Intensification (SRI) and the Minus-one Nutrient Technique are examples of recent rice farming technologies that are proven to be less capital intensive.